Functionalized Three–Dimensional Graphene Containing Chitosan and Bovine Serum Albumin for Recognizing Chiral Drug Intermediates - Sha Li; Wenyan Yao; Licheng Xie; Yan Jiang (Chemosensors, 2023)
Chiral enantiomer recognition has important research significance in the field of analytical chemistry research. At present, most prepared chiral sensors are used for recognizing amino acids, while they are rarely used in the identification of drug intermediates. This work found that combining CS and reduced graphene oxide can enhance conductivity, increasing the recognition effect by connecting CS with BSA. Based on the above preparation, a new type of chiral sensor (3D–rGO–CS–BSA) was synthesized for the identification of drug intermediates, including the 1–Boc–3–hydroxypyrrolidine enantiomer. An obvious difference was achieved (IR/IS = 2.82) in the oxidation peak currents between the two enantiomers. The detection limits of the R–enantiomer and S–enantiomer were 4.85 nM and 11.76 nM, respectively. The proposed electrochemical sensing platform also has better potential for detecting the percentage content of mixed chiral enantiomer drugs.